The filling factor of the sEMG signal at low contraction forces in the quadriceps muscles is influenced by the thickness of the subcutaneous layer - Rodriguez-Falces, Javier; Malanda, Armando; Mariscal, Cristina; Navallas, Javier (Frontiers in Physiology, 2024)
It has been shown that, for male subjects, the sEMG activity at low contraction forces is normally "pulsatile", i.e., formed by a few large-amplitude MUPs, coming from the most superficial motor units.The subcutaneous layer thickness, known to be greater in females than males, influences the electrode detection volume. Here, we investigated the influence of the subcutaneous layer thickness on the type of sEMG activity (pulsatile vs continuous) at low contraction forces. Voluntary surface EMG signals were recorded from the quadriceps muscles of healthy males and females as force was gradually increased from 0 to 40% MVC. The sEMG filling process was examined by measuring the EMG filling factor, computed from the non-central moments of the rectified sEMG signal. The main findings were: (1) The sEMG activity at low contraction forces was "continuous" in the VL, VM and RF of females, whereas this sEMG activity was "pulsatile" in the VL and VM of males. (2) The filling factor at low contraction forces was lower in males than females for the VL (p=0.003) and VM (p=0.002), but not for the RF (p=0.54). (3) The subcutaneous layer was significantly thicker in females than males for the VL (p=0.001), VM (p=0.001), and RF (p=0.003). (4) A significant correlation was found in the vastus muscles between the subcutaneous layer thickness and the filling factor (p<0.05). The present results indicate that the sEMG activity at low contraction forces in the female quadriceps muscles is "continuous" due to the thick subcutaneous layer of these muscles, which impedes an accurate assessment of the sEMG filling process.